Textual Metadiscourse in Academic Book Reviews in Serbian and English - Vučićević, Ana Lj.; Rakić, Aleksandra D. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
This paper examines the forms and patterns of use of the markers of textual metadiscourse in the academic book reviews from the fields of humanities (linguistics and literature) and social sciences (sociology, history, and ethnography) in both Serbian and English languages. The principal aim of our research was to attempt to establish a potential variation in the use of these markers with regard to the parameters of the type of markers, discipline, and language in which the reviews were written. The qualitative-quantitative analysis was carried out according to the model provided by Blagojević (2008). As for the first parameter, the comparison showed the predominance of logical textual connectives in comparison to both other textual connectives and markers of discourse actions/references to discourse across disciplines and languages. When it comes to the parameter of discipline, linguistics, literature and sociology reviews contained the greatest number of markers. Regarding the language criterion, cumulatively speaking, more markers were observed in the reviews in Serbian than in the reviews in English. However, the difference was rather subtle and it pointed to similarities rather than disparities in the use of these markers.
Keywords: academic discourse; academic book reviews; textual metadiscourse; disciplines; Serbian; English